Thyroid metastasis from nasopharyngeal cancer: a case report - D. M. Fatkullin; A. O. Guz; A. V. Garev; A. S. Zakharov; M. I. Sokolova; I. G. Shesler; K. S. Aristarkhova (Сибирский онкологический журнал, 2023)
Background. Nasopharyngeal cancer is a rare head and neck cancer with a relatively high risk of locoregional recurrence and distant metastases. The most common sites of metastases are bones (70–80 %) followed by liver (30 %), lung (18 %), and lymph node (axillary, mediastinal, pelvic, and inguinal). Thyroid gland is an uncommon site of metastasis with an incidence ranging from 0.5% to 24 %. Thyroid metastasis from nasopharyngeal cancer has been reported in only 9 cases in the world literature and no one in Russia. Case report. We report a case of thyroid metastasis from nasopharyngeal cancer found incidentally in a 53-year-old female patient. Conclusion. Metastases to the thyroid gland are rare, and patients with metastatic thyroid disease rarely present with organ-specifc symptoms, thus raising diagnostic diffculties for both clinicians and the pathologists. This clinical report demonstrates the diffculties of differential diagnosis,as well as the importance of a thorough collection of complaints, anamnesis, and clinical examination.